2016
DOI: 10.20852/ntmsci.2016318930
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient bounds for new subclasses of bi-univalent functions

Abstract: In the present paper, introduction of new subclasses of bi-univalent functions in the open disk was defined. Moreover,by using Salagean operator,in these new subclasses for functions, upper bounds for the second and third coefficients were found. Presented results are a generalization of the results obtained by Srivastava et al.[12], Frasin and Aouf [7] and Ç aglar et al.[5].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A function f 2 A is said to be bi-univalent in E if f and f 1 are univalent in E. Let be the class of bi-univalent functions in E which is given by (1.1). Lewin [14] investigated the bi-univalent function class and showed that ja 2 j < 1:51: For an interesting examples and a brief history in the class ; see [15] ( see also [15,16,17,18,19,20,21,22,23,24]).…”
Section: Introductionmentioning
confidence: 99%
“…A function f 2 A is said to be bi-univalent in E if f and f 1 are univalent in E. Let be the class of bi-univalent functions in E which is given by (1.1). Lewin [14] investigated the bi-univalent function class and showed that ja 2 j < 1:51: For an interesting examples and a brief history in the class ; see [15] ( see also [15,16,17,18,19,20,21,22,23,24]).…”
Section: Introductionmentioning
confidence: 99%
“…They introduced bi-starlike functions and bi-convex functions and obtained estimates on the initial coefficients. Also the subclasses of bi-univalent functions defined by Salagean operator were studied by various authors [3,9,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…For a brief history and interesting examples in the class Σ, see [25] (see also [5], [6], [13], [16]). Furthermore, judging by the remarkable flood of papers on the subject (see, for example, [11], [23] and [24]). Not much is known about the bounds on the general coefficient |a n | .…”
Section: Introductionmentioning
confidence: 99%